The Impact of An Instructional Program on Hypothyroidism Patients’ Knowledge Toward Physical Exercise and Activity Daily Livings - Mohammed AL Aqeeli; Hakima Hassan (Kufa Journal for Nursing Sciences)
ABSTRACT: